La enfermedad cuero de sapo en yuca (Manihot esculenta Crantz) - Pineda López, Benjamín; Jayasinghe, W. Upali; Lozano, J.C. (1983)
The importance, symptomatology, and etiology of the frog skin disease in cassava are briefly described. This disease has caused losses up to 90 percent or more in Quilcace, Tambo (Cauca) and other municipalities of Colombia. The 1st symptoms of the disease appear 50-60 days after planting in cuttings taken from diseased plants. Small, longitudinal, deep fissures resulting in lip-shaped lesions, generally in the callus region, are detected. Storing parenchyma is reduced as well as starch grains. The no. of well- developed xylem vessels increases and there is degradation of the phloem cell which appears to be blocked by massive inclusions. The periderm is thick and corky. The disease can be diagnosed 50 days after planting with a magnifying glass, later on at simple sight, especially on recently harvested roots. A technique to detect the disease by electrophoresis has been developed. In endemic regions cuttings from the most severely affected, vigorous plants (thickest stems) are selected. Other methods of dissemination have been studied. Etiologically it seems to be a pathogenic disease with viral characteristics. The causal agent is currently beingcharacterized. The following control measures are recommended: removal of all sources of inoculum, crop residues, or diseased plants, and elimination of weeds; use of disease-free material from healthy plantations, preferably meristems; disinfestation of tools with water and detergent; quarantine measures. (CIAT)